2016
DOI: 10.1242/dev.128892
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent chromatin remodeling during mammalian development

Abstract: Precise gene expression ensures proper stem and progenitor cell differentiation, lineage commitment and organogenesis during mammalian development. ATP-dependent chromatin-remodeling complexes utilize the energy from ATP hydrolysis to reorganize chromatin and, hence, regulate gene expression. These complexes contain diverse subunits that together provide a multitude of functions, from early embryogenesis through cell differentiation and development into various adult tissues. Here, we review the functions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 182 publications
(244 reference statements)
1
175
0
1
Order By: Relevance
“…ES cells completely devoid of MTA proteins are complete NuRD nulls and are viable but show inappropriate expression of differentiation-associated genes, are unable to maintain an appropriate differentiation trajectory and do not contribute to embryogenesis in chimaeric embryos. Protein subunit diversity is often found in chromatin remodelling complexes which specifies functional diversity (Hargreaves & Crabtree, 2011;Morey et al, 2012;Hota & Bruneau, 2016). This is also the case for the NuRD complex, where alternate usage of Mbd2/3, Chd3/4/5 and Mta1/2/3 has been found to result in alternate functions for NuRD complexes (Feng & Zhang, 2001;Fujita et al, 2003;Nitarska et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ES cells completely devoid of MTA proteins are complete NuRD nulls and are viable but show inappropriate expression of differentiation-associated genes, are unable to maintain an appropriate differentiation trajectory and do not contribute to embryogenesis in chimaeric embryos. Protein subunit diversity is often found in chromatin remodelling complexes which specifies functional diversity (Hargreaves & Crabtree, 2011;Morey et al, 2012;Hota & Bruneau, 2016). This is also the case for the NuRD complex, where alternate usage of Mbd2/3, Chd3/4/5 and Mta1/2/3 has been found to result in alternate functions for NuRD complexes (Feng & Zhang, 2001;Fujita et al, 2003;Nitarska et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Protein subunit diversity is often found in chromatin remodelling complexes which specifies functional diversity (Hargreaves & Crabtree, ; Morey et al , ; Hota & Bruneau, ). This is also the case for the NuRD complex, where alternate usage of Mbd2/3, Chd3/4/5 and Mta1/2/3 has been found to result in alternate functions for NuRD complexes (Feng & Zhang, ; Fujita et al , ; Nitarska et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of ATP‐dependent chromatin remodelling complexes contribute to cardiac development and function, congenital heart defects and/or cardiovascular diseases such as cardiomyopathy, heart failure, atherosclerosis and pulmonary hypertension (Clapier and Cairns, ; Han et al , ; Vallaster et al , ; Rosa‐Garrido et al , ; Hota and Bruneau, ). Increasing evidence suggests that ROS can affect the function of these complexes at different levels.…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…BAF60C is not expressed in ES cells but is up-regulated during mesoderm formation, where it is required for proper cardiac development and skeletal muscle differentiation [98, 143]. The combinatorial composition of subunits within chromatin remodeling complexes of the SWI/SNF family has an important role in the modulation of the activity of these ATP-dependent enzymes (reviewed by [144]), and inclusion of BAF60C in these complexes during gastrulation may be associated with chromatin remodeling of specific sites important for mesodermal patterning. Although there are no genome wide studies validating the function of BAF60C at MYOD sites, studies from the Tapscott lab demonstrated that both Myf5 and MyoD bind similar loci and induce chromatin remodeling through an increase in acetyl-histone 4 (H4Ac) levels [21, 101], but only MyoD binding is associated with recruitment of RNA pol II and robust transcription.…”
Section: Requirement Of a Mesodermal Intermediate And Differencesmentioning
confidence: 99%